Analysis of the vo2max physical condition of tarung derajat athletes through yoyo test: Preparation for pre-PON XX - Novi Yanti; Uray Gustian; Ruslan Abdul Gani; Edi Setiawan (UIR Press, 2022)
During the current Covid-19 pandemic crisis, it found that Vo2max possessed by Tarung Derajat athletes has decreased significantly during training, therefore the purpose of this study was to analyze the level of Vo2max physical condition of Tarung Derajat athletes. This study used a quantitative approach through the survey method. The sample in this study were all Tarung Derajat martial arts athletes who took part in the XX Pre-PON championship, with a total of 24 athletes. This study used total sampling technique and obtained 24 athletes as samples. The instrument applied in this study was Yoyo Test and data were analyzed by using Microsoft Excel 2010. The results showed that most of the female athletes had a poor physical condition, while the physical condition of some male athletes was in the good category, some were in the very good category. Thus, it was still need an improvement, especially studies in the preparation of training programs, in improving physical condition, particularly for female athletes. The contribution of the results of this research will be able to increase understanding and information for trainers in order to achieve maximum performance.